(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The aspiration of this article is to critically confer on Islamic education teachers (IETs) critical thinking issues in schools. The valuation of IET’s critical thinking skills lies in the cultural excellence of the knowledge and professionalism that it presents. Currently, the impact of western lines of thought that monopolize the secular education system can be deleterious to the Muslims’ belief if we are not aware of this secular thought. Hence, the Quranic and Sunnah-based knowledge and the competency of disparate skills among IETs can vanquish any inimical impact on the students’ thinking specifically. Hence, in order to foster a generation who are high-skilled, able to perform critical thinking, collaborative, exhibiting high creativity, competent communicators, and having high emotional well-being, IETs have to implement measures adopting a diversity of skills and teaching aids to promote 21st-century teaching and facilitation (T & F). This article desires to examine IETs critical thinking practices and their challenges in enhancing 21st-century learning. This paper too presents the apposite Islamic Studies (IS) T & F in the era of the 4.0 Industrial Revolution based on the components of the culture of lifelong knowledge, ICT skills, higher order thinking skills (HOTs), and knowledge integration in the 21st century T & F. The present challenges experienced by IETs in materializing 21st-century learning in the era of the 4.0 Industrial Revolution are also explored.